Ofatumumab with iphosphamide, etoposide and cytarabine for patients with transplantation‐ineligible relapsed and refractory diffuse large B‐cell lymphoma. (1st April 2022) - Paszkiewicz‐Kozik, Ewa; Michalski, Wojciech; Taszner, Michał; Mordak‐Domagała, Monika; Romejko‐Jarosińska, Joanna; Knopińska‐Posłuszny, Wanda; Najda, Jacek; Borawska, Anna; Chełstowska, Monika; Świerkowska, Monika; Dąbrowska‐Iwanicka, Anna; Malenda, Agata; et al.
Summary: The efficacy of salvage treatment of diffuse large B‐cell lymphoma (DLBCL) patients who relapse or progress (rrDLBCL) after initial therapy is limited. Efficacy and safety of ofatumumab with iphosphamide, etoposide and cytarabine (O‐IVAC) was evaluated in a single‐arm study. Dosing was modified for elderly patients. Patients received up to six cycles of treatment. The primary end‐point was the overall response rate (ORR). Patients were evaluated every two cycles and then six and 12 months after treatment. Other end‐points included progression‐free survival (PFS), event‐free survival (EFS), overall survival (OS) and safety. Seventy‐seven patients received salvage treatment with O‐IVAC. The average age was 56.8 years; 39% had an Eastern Cooperative Oncology Group (ECOG) performance status of at least 3; 78% had disease of Ann Arbor stage 3 or 4; 58% received one or more prior salvage therapies. The ORR for O‐IVAC was 54.5%. The median duration of study follow‐up was 70 months. The median PFS and EFS were 16.3 months each. The median OS was 22.7 months. Age, ECOG performance status and the number of prior therapy lines were independent predictors of survival. Treatment‐related mortality was 15.5%. O‐IVAC showed a high response rate in a difficult‐to‐treat population and is an attractive treatment to bridge to potentially curative therapies.